Detailed NOX precursor measurements within the reduction zone of a novel small-scale fuel flexible biomass combustion technology. (15th October 2021) - Archan, Georg; Scharler, Robert; Pölzer, Leonhard; Buchmayr, Markus; Sommersacher, Peter; Hochenauer, Christoph; Gruber, Johann; Anca-Couce, Andrés
Highlights: Development of a fuel flexible biomass combustion technology with low emissions. NOX emissions minimized at reduction zone air ratios between 0.8 and 0.95. Gas temperature, NO, HCN and NH3 distribution measured within the reduction zone. Unexpected opposite trend of HCN/NH3 ratio compared to typical grate combustion. Identified mechanisms to minimize NOX emissions with novel technology. Abstract: A novel biomass combustion technology with a compact fixed-bed operated with a low oxygen content and double air staging was investigated. Minimized flue gas emissions at high fuel flexibility were achieved only with primary measures. The fuel nitrogen conversion mechanisms were investigated in detail in the secondary zone of a 30 kW lab-reactor, designed as efficient reduction zone. Experimental investigations were carried out to determine the distribution of gas temperatures, main dry product gas components as well as NOX precursors such as NH3 and HCN along the height of the reduction zone. The objective was to determine and understand the various fuel nitrogen conversion mechanisms in the reduction zone that can minimize NOX emissions. It was found that the HCN/NH3 ratio increases with the fuel nitrogen content. This corresponds to an unexpected opposite trend to typical biomass grate furnaces. It was concluded that it is crucial for the HCN/NH3 ratio whether the released nitrogen tars are already cracked in the fixed-bed or only in the gas phase, as in the novel technology. Furthermore, the influence of gas temperature, air ratio, mixing, recirculated flue gas and residence time on the formation and reduction of NH3, HCN and NO is discussed. Finally, this novel technology achieves NOX emissions of<95 mg·m −3 and 175 mg·m −3 for woody and herbaceous fuels, respectively, which is well below the small-scale state-of-the-art for the respective N contents and it achieves fuel nitrogen conversions to NOX in flue gas of 35% and 25%, respectively.